2012
DOI: 10.1097/ta.0b013e31822a2f2b
|View full text |Cite
|
Sign up to set email alerts
|

Influence of flap factors on partial necrosis of reverse sural artery flap

Abstract: Probability of partial necrosis occurring in reverse sural artery flap significantly increase when top-edge of the flap locates in the upper 1/9 of the calf, when LWR of the flap is 5:1 or more, or when width is 8 cm or more. The flap with top-edge locating lower 7/9 of the calf is safe and reliable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 26 publications
4
53
0
Order By: Relevance
“…In a large study of 179 reverse sural artery flaps by Wei et al in 2012 it was observed that partial flap necrosis occurred in 11.2% of cases. They concluded that partial necrosis rate was significantly higher in the flaps with top edge locating in the upper 1/9 of the calf, in the flaps with length-width ratio (LWR) ≥ 5 : 1 and in the flaps with width of skin island (width) ≥ 8 cm [23]. The major disadvantage of this flap is the scarification of the sural nerve leading to anaesthesia of the lateral foot.…”
Section: Discussionmentioning
confidence: 99%
“…In a large study of 179 reverse sural artery flaps by Wei et al in 2012 it was observed that partial flap necrosis occurred in 11.2% of cases. They concluded that partial necrosis rate was significantly higher in the flaps with top edge locating in the upper 1/9 of the calf, in the flaps with length-width ratio (LWR) ≥ 5 : 1 and in the flaps with width of skin island (width) ≥ 8 cm [23]. The major disadvantage of this flap is the scarification of the sural nerve leading to anaesthesia of the lateral foot.…”
Section: Discussionmentioning
confidence: 99%
“…20 Reported necrosis (including partial and complete necrosis) rates of the flap ranged from 4.8 to 36.0%. 1,9,17,[20][21][22][23] In pediatric patients, the necrosis rate was reported to be 5% (1/20) by Koladi et al 13 and 12.5% (2/16) by Vergara-Amador. 14 In this study, there was no complete flap necrosis; partial necrosis rate was 13.2% (7/53, pediatric group) and 12.2% (18/148, adult group), and marginal necrosis rate was 3.8% (2/53) and 1.4% (2/148).…”
Section: Discussionmentioning
confidence: 92%
“…The topedge location, compared with other flap factors including the total length, width of the skin island, and length-width ratio, was a better parameter for the evaluation of the influence of flap factors on the complications in the children and adults. 17 In this study, the top-edge location in both groups was comparable, and all the flap surgeries were performed by the senior author (Z.G.D.). In summary, the patient, flap, and operator factors have minor interference with the comparative outcomes of the complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations